Ekološke značilnosti habitatov in potencialna razširjenost izbranih kvalifikacijskih gozdnih vrst hroščev (Coleoptera) v okviru omrežja Natura 2000 v Sloveniji - Vrezec, Al (Gozdarski vestnik, 2014)
In this paper the first attempt of large scale habitat evaluation in Slovenia is given for four forest beetle species of European conservation concern: Rosalia alpina, Morimus funereus, Cucujus cinnaberinus, and Lucanus cervus. From selected large-scale databases the habitat selection characteristics were analysed and maps of potential forest habitat suitability were developed. The maps were validated in the field. From this turn out only the spatial model for Rosalia alpina appeared to be acceptable. The analysis of proportion of inclusion of potential areal of selected beetle species into current Natura 2000 network revealed some deficiencies. The present first models developed for Natura 2000 species are presented should be improved by supplementation of data and improvement of more targeted samplings in future studies. It is advised to use the same method for other Natura 2000 qualification species as well.
Keywords: Natura 2000; prostorski modeli; habitati; alpski kozliček; bukov kozliček; škrlatni kukuj; rogač; Rogač, Šolta; Slovenia; Slovenija